2018
DOI: 10.1007/s40152-018-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Narrative assemblages for power-balanced coastal and marine governance. Tara Bandu as a tool for community-based fisheries co-management in Timor-Leste

Abstract: Poverty alleviation and resource governance are inextricably related. Mainstream resource management has been typically criticized by social scientists for the inherent power imbalances between fishery managers and small-scale fishing communities. Yet, while a number of mechanisms of collective action to address these power imbalances have been developed, they remain undertheorized. This paper builds upon first-hand experience of the authors in assisting the community of Biacou to strengthen the resource manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Whilst it is often framed by NGOs as a longstanding and important tradition, tara bandu (as with other similar customary institutions e.g., Cohen and Steenbergen, 2015) has undergone a process of contemporary revitalization and re-imaging since independence (McWilliam et al, 2014;Alonso-Población et al, 2016. Observers have suggested that the application of tara bandu in managing natural resource use is merely appropriation of the institution to achieve externally formulated conservation and sustainability objectives (McWilliam et al, 2014), and its nature and presence in between governing systems reflects the presence of a legal pluralism (Alonso-Población et al, 2018). Nonetheless, tara bandu appears to hold legitimacy with communities, NGOs and government alike (see Table 1) and its invocation in communitybased resource management or co-management seems almost inevitable.…”
Section: Community-based Institutionsmentioning
confidence: 99%
“…Whilst it is often framed by NGOs as a longstanding and important tradition, tara bandu (as with other similar customary institutions e.g., Cohen and Steenbergen, 2015) has undergone a process of contemporary revitalization and re-imaging since independence (McWilliam et al, 2014;Alonso-Población et al, 2016. Observers have suggested that the application of tara bandu in managing natural resource use is merely appropriation of the institution to achieve externally formulated conservation and sustainability objectives (McWilliam et al, 2014), and its nature and presence in between governing systems reflects the presence of a legal pluralism (Alonso-Población et al, 2018). Nonetheless, tara bandu appears to hold legitimacy with communities, NGOs and government alike (see Table 1) and its invocation in communitybased resource management or co-management seems almost inevitable.…”
Section: Community-based Institutionsmentioning
confidence: 99%
“…Cultural institutions and social practices that operate in wider contexts than the fishing sector are key to how people understand and use fishery resources. Customary systems of resource access and distribution, for example, are common across coastal communities in the region and often enacted through societal hierarchies (Alonso‐Población, Rodrigues, Wilson, Pereira, & Lee, ; Cohen & Steenbergen, ). Fishing and trading behaviour in such cases may not only reflect economically rational decision‐making, but also indicate strong underlying social rules, dependencies and accountabilities to which people are subject.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Within the supply GS local social networks in and among communities that form around kinship relations, central points of local authority (power) and/or historical social ties between individuals, strongly influence the distribution of fishing capacity (Alonso Población, ; Alonso Población, Rodrigues, & Lee, ). Often smaller social groups in coastal villages enjoy higher customary status through their roots in particular traditional kinship structures (Alonso‐Población et al, ). Such power hierarchies often appear through contemporary forms of formal village leadership (i.e.…”
Section: Case‐studiesmentioning
confidence: 99%
“…Articles in this journal have included previous work by Charles Menzies (, , , ), who is a contributor to the current special issue. In the last few decades, along with other social scientists, a number of anthropologists have attended to the contemporary and historical impacts of ecological crises on human workers formerly reliant on specific wild seafood stocks, including the imposition of government‐mandated moratoria (e.g., Davis ), impacts of major infrastructure projects such as dams on humans’ work on river systems (e.g., Lansing et al ), the growth of aquaculture (e.g., Cruz‐Torres ; Meltzoff et al ), and interactions between coastal populations and governments with respect to sustainable resource management (Alonso Población et al ; Davis et al ; Durrenberger ; Durrenberger and King ; García Allut ; McCay ; Meltzoff ; Pita et al ). As well, there has been some important anthropological research, although far less, dealing with individuals working on cargo vessels (e.g., Borovnik ) and on transitions of coastal economies from seafood harvesting to tourism and pilgrimage (e.g., Herrero and Roseman ; Nadel‐Klein ).…”
Section: Ethnography and Working On Watermentioning
confidence: 99%